Strikes in France and the Netherlands; A Comparison of Labour Market Institutions - Frank A.G. den Butter; Silvie Y. Koppes (Tinbergen Institute, 2003)
Strikes as a consequence of labour conflicts occur about 28 times as much in France as in the Netherlands. This paper examines the institutional differences underlying these differences in strike activity. Our empirical analysis shows that strike activity is high in France if workers were successful in obtaining relatively high wage increases in collective labour agreements in the previous year, whereas strike activity is high in the Netherlands if, in the preceding year, real wage increases were relatively low as compared to productivity increases. Moreover it appears that the influence of strikes on wage formation on a macro-level is much higher in France than in the Netherlands.
Keywords: J31; J52; 330; Strikes; Comparative analysis of policy institutions; Wage formation; Arbeitskampf; Institutionelle Infrastruktur; Niederlande; Frankreich